Effects of ground-based skidding on soil physical properties in skid trail switchbacks - Solgi, Ahmad (Array, 2019)
Effective skid-trail design requires a solid understanding of vehicle-soil interactions, yet virtually no data exist on the effects of harvest traffic on soils in the switchback curves common in mountainous terrain. We contrast for the first time the effect of skidding on dry bulk density, total porosity, macroporosity, and microporosity in the straight segments of the skid trail and in various positions within switchbacks of differing trail curvature (deflection angle) on different slope gradients. Treatment plots with three replications included combinations of two classes of curvature (narrow = high deflection angle, 60–70°; wide = low deflection angle, 110–130°) and two categories of slope gradient (gentle = ≤20%; steep = >20%). The Cambisol soil was sampled in control and trafficked areas both before and after three passes with a rubber-tired skidder. After only three passes, significant effects were seen for dry soil bulk density (+), total porosity (–), macroporosity (–), and microporosity (+), with steady trends from undisturbed controls to straight segments to wide curves to narrow curves. Soil damage increased gradually and consistently toward the apex of the curve, particularly in narrow curves on gentle slopes. Our results establish that curvature and switchback position are important factors affecting soil compaction in ground skidding. The strong observed effects of even low harvest traffic volume on soil physical properties in curves indicate that the degree of soil compaction in skid trails may be underestimated in areas with numerous switchbacks, the placement of which within a skid trail system may require careful consideration on mountainous terrain.